PENERAPAN MODEL COOPERATIVE LEARNING TIPE PICTURE AND PICTURE DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK SEKOLAH DASAR - Elsa Kania Hasibuan; Sri Rahmi Tanjung; Aprilia Eka Putri; Laura Delvi (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to determine (1) the effect of the cooperative learning modelon learning motivation (2) the effect of cooperative learning models on learning outcomes (3)the relationship between motivation and learning outcomes that are learned using the model cooperative learning. This research is a quasi-experimentalCooperative learning is known as open learning. However, cooperative learning is more than just group learning or group work because in cooperatives there is a cooperative drive or task that allows open interaction and effective interdependence among group members.Cooperative learning can also be interpreted as a shared task structure in an atmosphere of togetherness among fellow group members. Cooperative learning is a learning model where the system learns and works in small groups that gather 4-6 people collaboratively so that it can make students more enthusiastic in learning